L'Ustica Del Mari . The Moby Prince History - Moschin, Claudio (Claudio Moschin, 2006)
Verzio FF submission 140 victims, zero guilty. Fifteen years ago, a few miles from the Livorno’s seaport, the ferry-boat Moby Prince crashed against an oil tanker, named Agip Abruzzo: “human error”said the technicians and the experts. This film examines what happened fifteen years after the event.